Two new species of Phyllachora and a new host record for P. pogonatheri on the subtribe Saccharinae from Southwest China - Li, Xiao-Ling; Liu, Qin; Zhang, Shu Ting; Liu, Jun Rong; Wang, Jin Feng; Lu, Wen Hua; Li, Cheng Yun (Phytotaxa, 2026)
Two new graminicolous species of Phyllachora associated with hosts of the subtribe Saccharinae (Poaceae) (Phyllachora erianthi-rufipili on Erianthus rufipilus and P. spodiopogonis-sagittifolii on Spodiopogon sagittifolius) are described and illustrated from Yunnan Province, Southwest China. Species delimitation was based on morphological characteristics, molecular phylogenetic analyses, and host association. A high degree of host specificity was observed among Phyllachora species associated with Saccharinae grasses. In addition to the two new species, Pogonatherum crinitum is reported as a new host for Phyllachora pogonatheri. Furthermore, a modified CTAB method optimized for total DNA extraction of graminicolous Phyllachora is presented.